Evaluation of the QuantiFERON SARS-CoV-2 interferon-ɣ release assay in mRNA-1273 vaccinated health care workers - Krüttgen, Alexander; Klingel, Hanna; Haase, Gerhard; Haefner, Helga; Imöhl, Matthias; Kleines, Michael (Journal of virological methods, 2021)
•44 % of vaccinees had INF-ɣ levels above 015 IU/mL in response to stimulation.•100 % of vaccinees showed INF-ɣ levels above 0015 IU/mL in response to stimulation.•More studies are needed to set an appropriate cut-off for this convenient assay. Current studies focus on cellular and humoral immunity induced by novel SARS-CoV-2 vaccines. Non-responders to vaccinations are not uncommonly encountered in clinical medicine (e.g. in the field of hepatitis B). Whereas vaccine-induced humoral immunity against SARS-CoV-2 is compromised by emerging Variants of Concern (VOCs), cellular immunity against SARS-CoV-2 is emerging as resilient against VOCs. Thus commercially available test kits for diagnostic laboratories designed to evaluate cellular immune responses to SARS-CoV-2 are urgently needed. Here we evaluated the novel QuantiFERON SARS-CoV-2 assay (Qiagen) measuring INF-ɣ release induced by two spike-derived peptide pools (Ag1 and Ag2) in a cohort of health care workers vaccinated with the mRNA-1273 vaccine and confirmed humoral response. Our study indicates the usefulness of this novel assay for routine laboratories to evaluate cellular immunity against SARS-CoV-2 in response to mRNA-1273 vaccination.